First reported case of disseminated Microascus gracilis infection in a lung transplant patient. (2020) - Ding, Yanna; Steed, Lisa L.; Batalis, Nicholas
Abstract: Microascus gracilis is a specie of the genus Microascus in the family of Microascaceae and has been isolated from lung. It has never been reported as the cause of disseminated infection in humans. Herein, we report a fatal case of disseminated Microascus gracilis infection in a 65-year-old man with a history of primary idiopathic pulmonary fibrosis, status-post bilateral lung transplant. His course was complicated by donor lung cultures positive for multiple organisms and persistent pleural effusions. Multiple lung biopsy and bronchial lavage specimens were negative for mold. Later, pleural fluid cultures grew M. gracilis confirmed by DNA sequencing. Despite aggressive antifungal treatment, the patient continued to deteriorate with altered mental status. Imaging showed scattered hemorrhagic and hypodense lesions in the brain. The patient eventually succumbed to his infections and a restricted autopsy was performed. Autopsy findings included multiple hemorrhagic foci and abscesses involving the whole brain. Numerous punctuate, tan-white circular lesions were on the endocardium and diffuse tan exudates covered the pericardium and lungs. Histologically, similar fungal organisms with septate branching hyphae and short chains of conidia were identified, along with hemorrhage, neutrophilic inflammation, and necrosis in the brain, pleura, peripheral parenchyma of lungs and heart. This is the first reported case of disseminated M. gracilis infection in an immunosuppressed human, indicating it can cause localized infections and disseminated infections. This case increases our awareness of such fatal opportunistic infections, particularly in lung transplant patients, and urges earlier aggressive prophylaxis, diagnosis, and treatment.